ALFAC (aquatic literacy for all children) project: how to prevent and engage 6-12 year olds children in europe in aquatic environment - Mekkaoui, L. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
Aquatic activities (AA) are promoted for their health benefits1. However, these benefits can be tragically overshadowed if children are not empowered with protective skills against drowning. The age group most at risk of this tragic event, which affects 37,000 lives per year in Europe, is the 5-14-year-old age group2. To tackle the dual aquatic issue of protection and involvement in AA, a partnership has been built between researchers, educators, and stakeholders from Europe around the ALFAC project, co-funded by the European Commission. The project goal is to improve the quality of aquatic education while increasing the Aquatic Literacy (AL) levels of children aged 6-12. The aim of this presentation is to present the construction of a holistic European test battery around an innovative theoretical framework: AL.